Diagnostics of Plant Diseases - Kurouski, Dmitry; Kurouski, Dmitry (IntechOpen, 2021)
Digital farming is an approach to farming in which crop yield is maximized while environmental impact is minimized. Integral to this approach is diagnostic sensing of plant disease and stress. This book examines innovative sensing technology such as satellite- and unmanned aerial vehicle (UAV)-based RGB and thermography imaging as well as hyperspectral, infrared, reflectance and Raman spectroscopy.
English
Keywords: Plant pathology & diseases